الدِّلالات الضدّيّة للصّيغ التّكليفيّة عند الأصوليين - عطّافي, عادل (جامعة الوادي - university of Eloued, 2022)
إنّ هذه الدّراسة المَوسومة بالدّلالات الضّدية للصّيغ التّكليفيّة عند الأصوليين، هي بحث في المنهج الأصولي المُعتمد في دراسة دلالات صيغ التّكليف، من حيث دلالة صيغ الأمر والنّهي على أضدادها، إذ تسعى الدراسة إلى الوقوف على المَنهجية التي اعتمدها الأصوليون في تحديد دلالة الأمر على النّهي عن أضداد المأمور به، ودلالة النّهي على الأمر بأضداد المنهي عنه، فتهدف إلى الكشف عن فكر لغوي تداولي عند الأصوليين، لم يسبقهم إليه أحد من الباحثين واللغويّين، من حيث استنباطهم لفعل كلامي جديد، يُمكن إدراجه ضمن نظرية الأفعال الكلامية في الدراسات التداولية المُعاصرة، وهو الفعل المُستلزم بالقول. This study ,entitled ‘’ the opposite meanings of order and interdiction formulas in the fundamentalists”, is a research in the fundamentalist approach adopted in the study of the indications of the formulas of commissioning, in terms of the significance of the forms of command and the prohibition on its opposites. The study seeks to identify the methodology adopted by the fundamentalists in determining the significance of the command on the prohibition on the opposites of what’s ordered, and the significance of the prohibition on the command by the opposites of what’s prohibited. It is intended to reveal the linguistic deliberative thinking of the fundamentalists, which was not preceded by any researcher or linguist before, in terms of their development of a new verbal act, which can be included within the theory of verbal acts in the contemporary delibrative studies, which is the act required by saying.
مقال
Keywords: الدّلالات الضدية؛ الأمر؛ النّهي؛ الأصوليون; Fundamentalists ؛interdiction ؛ order ؛ the opposite meanings